1974
DOI: 10.1017/s0373463300029192
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Air Navigation

Abstract: With the growth of public air transport, safety in the air is a matter of concern not just to those who design, manufacture and operate aircraft, but to the public at large. After an accident has occurred and an unfortunate chain of events leading to the accident is exposed, it may be easy to say ‘this accident should not have occurred’ or ‘would not have occurred if…’. Publication of annual totals brings forth informed and uninformed comment on the apparent decrease or increase in the accident rate relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Yet, as in other circumstances, these catas trophic events attracted more public concern (if press publicity is to be taken as a measure of this) than the deaths of 6500 other road users in the same year (Sabey & Taylor 1980). Rather similarly, as table 1 confirms, air travel (measured in terms either of gross fatalities per 105 travelling or of fatalities per unit of distance travelled) is about six times safer than road travel (Stratton 1974). Yet because a high proportion of aircraft accidents have no survivors (57% of 1713 accidents to public transport aircraft in 1946-73) and because of the number of fatalities incurred in many individual incidents (37 accidents with over 100 victims in 1970-8), the public perception of flying, like that of motorway driving, as a dangerous form of travel has been sustained.…”
Section: Risks In Transportmentioning
confidence: 69%
“…Yet, as in other circumstances, these catas trophic events attracted more public concern (if press publicity is to be taken as a measure of this) than the deaths of 6500 other road users in the same year (Sabey & Taylor 1980). Rather similarly, as table 1 confirms, air travel (measured in terms either of gross fatalities per 105 travelling or of fatalities per unit of distance travelled) is about six times safer than road travel (Stratton 1974). Yet because a high proportion of aircraft accidents have no survivors (57% of 1713 accidents to public transport aircraft in 1946-73) and because of the number of fatalities incurred in many individual incidents (37 accidents with over 100 victims in 1970-8), the public perception of flying, like that of motorway driving, as a dangerous form of travel has been sustained.…”
Section: Risks In Transportmentioning
confidence: 69%
“…An analysis of fatal accidents (those in which at least one person was killed) for civil transport aircraft 1946-73, 6 showed that the number of mid-air collisions had not varied statistically significantly throughout the period, averaging at about 2-r per year. An analysis of fatal accidents (those in which at least one person was killed) for civil transport aircraft 1946-73, 6 showed that the number of mid-air collisions had not varied statistically significantly throughout the period, averaging at about 2-r per year.…”
Section: Flight Economicsmentioning
confidence: 99%
“…6 There is a further reason why it requires particular attention; many collisions between aircraft are between a small and a large aircraft in which only those in the small aircraft fail to survive. Without in any way detracting from the importance of maintaining at least the above high level of safety in mid-air collisions, aircraft collision with high ground, particularly in mountainous regions, is a much more serious and global risk.…”
Section: 32mentioning
confidence: 99%
See 2 more Smart Citations